2-(1H-Benzotriazol-1-yl)-1-(4-bromobenzoyl)ethyl 4-methylbenzoate - Jiu-Long Sun; Meng Wang; Ying-Jie Zhu; Fang Li; Sai Bi (Acta Crystallographica Section E, 2008)
In the molecule of the title compound, C23H18BrN3O3, the benzotriazole mean plane makes dihedral angles of 1.26 (1) and 87.39 (1)° with the tolyl and bromophenyl benzene rings, respectively, and the dihedral angle between the benzene rings is 87.27 (1)°. In the crystal structure, molecules are linked into chains along the a axis by C—H...O intermolecular hydrogen bonds. The structure is further stabilized by C—H...π and π–π interactions, with a distance of 3.700 (1) Å between the centroids of the bromophenyl and benzotriazole benzene rings related by symmetry code (x, −1 + y, z).